2010
DOI: 10.4049/jimmunol.1002330
|View full text |Cite|
|
Sign up to set email alerts
|

An Inflammasome-Independent Role for Epithelial-Expressed Nlrp3 in Renal Ischemia-Reperfusion Injury

Abstract: Cytoplasmic innate immune receptors are important therapeutic targets for diseases associated with overproduction of proinflammatory cytokines. One cytoplasmic receptor complex, the Nlrp3 inflammasome, responds to an extensive array of molecules associated with cellular stress. Under normal conditions, Nlrp3 is autorepressed, but in the presence of its ligands, it oligomerizes, recruits apoptosis-associated speck-like protein containing a caspase recruitment domain (Asc), and triggers caspase 1 activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
222
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(240 citation statements)
references
References 62 publications
15
222
3
Order By: Relevance
“…In the study by Sandanger, et al, 33) myocardial dysfunction and injury in response to I/R was signifi cantly improved in ex vivo Langendorff-perfused hearts isolated from NLRP3-KO mice compared with hearts isolated from wild-type and ASC-KO mice, suggesting different roles of NLRP3 and ASC in terms of myocardial damage after I/R. Similarly, Shigeoka, et al 34) showed that renal I/R injury was reduced in NLRP3-KO mice, but not in ASC-KO mice, and concluded that NLRP3 contributes to the development of renal I/R injury independent of the infl ammasome. We have also recently observed that hepatic I/ R injury was significantly ameliorated in NLRP3-KO mice, but not in ASC-KO mice.…”
Section: Nlrp3 Inflammasome and Myocardial Infarction (Mi)mentioning
confidence: 96%
“…In the study by Sandanger, et al, 33) myocardial dysfunction and injury in response to I/R was signifi cantly improved in ex vivo Langendorff-perfused hearts isolated from NLRP3-KO mice compared with hearts isolated from wild-type and ASC-KO mice, suggesting different roles of NLRP3 and ASC in terms of myocardial damage after I/R. Similarly, Shigeoka, et al 34) showed that renal I/R injury was reduced in NLRP3-KO mice, but not in ASC-KO mice, and concluded that NLRP3 contributes to the development of renal I/R injury independent of the infl ammasome. We have also recently observed that hepatic I/ R injury was significantly ameliorated in NLRP3-KO mice, but not in ASC-KO mice.…”
Section: Nlrp3 Inflammasome and Myocardial Infarction (Mi)mentioning
confidence: 96%
“…21,75 However, postischemic tubular necrosis depends on NLRP3 [76][77][78][79] but not on ASC. 76 This finding could imply an additional, inflammasome-independent, biologic effect of ASC in postischemic AKI. Studies performed on the model of acute oxalosis suggest inflammasome signaling to be restricted to intrarenal dendritic cells.…”
Section: Aki Modelsmentioning
confidence: 99%
“…3,[19][20][21] We and others have demonstrated primarily non-canonical and inflammasome-independent roles for NLRP3 in the kidney epithelium and during experimental kidney injury in vivo. [20][21][22][23] For example, Nlrp3 − / − mice undergoing renal ischemia/reperfusion or unilateral ureteric obstruction (UUO) display reduced epithelial apoptosis and tubular injury independent of a canonical inflammasome or caspase-1. [20][21][22][23] In the intestinal tract, non-canonical NLRP3 regulates IL-18 maturation as well as epithelial cell shedding in response to Salmonella infection.…”
mentioning
confidence: 99%
“…[20][21][22][23] For example, Nlrp3 − / − mice undergoing renal ischemia/reperfusion or unilateral ureteric obstruction (UUO) display reduced epithelial apoptosis and tubular injury independent of a canonical inflammasome or caspase-1. [20][21][22][23] In the intestinal tract, non-canonical NLRP3 regulates IL-18 maturation as well as epithelial cell shedding in response to Salmonella infection. 3 Despite these studies, the biology of NLRP3 and other inflammasomerelated genes in epithelial cells has yet to be fully elucidated.…”
mentioning
confidence: 99%